Visualizing Arc protein dynamics and localization in the mammalian brain using AAV-mediated in situ gene labeling - Avallone, Martino; Pardo, Joaquín; Mergiya, Tadiwos F.; Rájová, Jana; Räsänen, Atte; Davidsson, Marcus; Åkerblom, Malin; Quintino, Luis; Kumar, Darshan; Bramham, Clive R.; Björklund, Tomas (Frontiers in Molecular Neuroscience, 2023)
The activity-regulated cytoskeleton-associated (Arc) protein is essential for synaptic plasticity and memory formation. The Arc gene, which contains remnants of a structural GAG retrotransposon sequence, produces a protein that self-assembles into capsid-like structures harboring Arc mRNA. Arc capsids, released from neurons, have been proposed as a novel intercellular mechanism for mRNA transmission. Nevertheless, evidence for intercellular transport of Arc in the mammalian brain is still lacking. To enable the tracking of Arc molecules from individual neurons in vivo, we devised an adeno-associated virus (AAV) mediated approach to tag the N-terminal of the mouse Arc protein with a fluorescent reporter using CRISPR/Cas9 homologous independent targeted integration (HITI). We show that a sequence coding for mCherry can successfully be knocked in at the 5′ end of the Arc open reading frame. While nine spCas9 gene editing sites surround the Arc start codon, the accuracy of the editing was highly sequence-dependent, with only a single target resulting in an in-frame reporter integration. When inducing long-term potentiation (LTP) in the hippocampus, we observed an increase of Arc protein highly correlated with an increase in fluorescent intensity and the number of mCherry-positive cells. By proximity ligation assay (PLA), we demonstrated that the mCherry-Arc fusion protein retains the Arc function by interacting with the transmembrane protein stargazin in postsynaptic spines. Finally, we recorded mCherry-Arc interaction with presynaptic protein Bassoon in mCherry-negative surrounding neurons at close proximity to mCherry-positive spines of edited neurons. This is the first study to provide support for inter-neuronal in vivo transfer of Arc in the mammalian brain.